Burden, and trends of breast cancer along with attributable risk factors in Gulf Cooperation Council countries from 1990 to 2019 and its projections - Majed M. Ramadan; Heba A. Alkhatabi; Doaa Aboalola; Samkari Alaa; Rawiah A. Alsiary (PLoS ONE, 2025)
Introduction Breast cancer (BC) is a growing global public health concern, affecting millions of women worldwide. Gulf Cooperation Council (GCC) countries are no exception to this trend. Mortality rates in GCC nations are still high despite improvements in BC treatment. This article examines the changing picture of BC incidence, prevalence, and mortality in the GCC region from 1990 to 2019 and predictions up to 2030. Material and method Using data from the Global Burden of Disease study, we analyzed BC incidence, prevalence, and mortality rates per 100,000 individuals across different age groups and countries. Results The study reveals a significant rise in Age-Standardized Incidence Rates (ASIR) for breast cancer among females in Saudi Arabia from 1990 to 2019, with Oman experiencing the highest increase and Kuwait the highest decrease. Bahrain also saw a significant increase in male Age-standardized death rate (ASDR), despite all other countries experiencing a decrease. Also, the data demonstrated a statistically significant positive correlation between ASIR and Human Development Index (HDI), evident across all countries. Metabolic risk and tobacco use were identified as primary contributors. A ten-year BC prediction predicts a significant increase in female cases, with Saudi Arabia expected to experience the highest rise. Conclusion This study underscores the urgent need for improved BC awareness, early detection through screening programs, enhanced access to quality healthcare services, and the addressing of sociocultural barriers in the GCC countries.